PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PERUSAHAAN - Endang Sri Utami; Zaenal Wafa (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The goal of business organizations is not only to seek profit, but also to be responsible to society (people) and the earth (planet). The company's social and environmental activities reflect the company's overall social responsibility, enabling the company to grow sustainably. Financial performance information is needed to assess potential changes in economic resources in the future and predict the production capacity of existing resources. This study aims to analyze the influence of sustainability reports, namely the economic dimension (profit), environmental dimension (planet), and social dimension (people) variables on financial performance (Return on Assets). The index used as a guideline for sustainability reporting in this study is based on the Global Reporting Initiative (GRI) G4. The population of this research is mining sector companies. Sample selection uses the purposive sampling method with several specific criteria. The type of data used is secondary data. Data analysis using multiple linear regression analysis. The research results concluded that sustainability report disclosure in economic, environmental, and social aspects had a significant positive effect on financial performance as proxied by Return on Assets (ROA). The results of this study provide implications that sustainability issues have been considered as an important part of corporate business decision making to improve financial performance.